Directed self-assembly of block copolymers on chemical patterns: A platform for nanofabrication - Ji, Shengxiang; Wan, Lei; Liu, Chi-Chun; Nealey, Paul F. (Progress in polymer science, 2016)
Directed self-assembly (DSA) of block copolymers (BCPs) on lithographically defined chemically nanopatterned surfaces (or chemical patterns) combines advantages of conventional photolithography and polymeric materials and shows promise for meeting a sufficiently inclusive set of manufacturing constraints for applications in semiconductors and data storage. DSA attracts attention from both academia and industry and tremendous progress has been achieved in the past decade. This review highlights the development of DSA with an emphasis on efforts toward the integration of block copolymer lithography into the current lithographic process for the fabrication of devices for integrated circuits and bit-patterned media.